(untitled) (Journal of the College of Basic Education, 2026)
Sadness is the opposite of joy, and the Holy Quran mentions the word sadness for women, as God Almighty said: (So that her eyes may be comforted and she may not grieve) (Surat Al-Qasas: 13, and Surat Taha: 40), The return of the Prophet Moses (peace be upon him) to his mother, who had cast him into the Nile River by the command of God Almighty, out of fear for him from Pharaoh’s tyranny and his killing of him, so that she might be happy and not sad, Thus, God Almighty fulfilled His promise to her by preserving him, returning him to her safe and sound, bringing her joy, and relieving her distress and sorrow. We have examined this topic and its impact on women’s lives in the Holy Quran, the noble Prophetic traditions, and the opinions of scholars and other relevant sources, and the results are as follows: Introduction: This section includes a study of the meaning of sadness, both linguistically and technically. The first section: includes a study of grief in light of the noble verses that indicate it. The second section: This section included a study of the negative physical and psychological effects on her. Physically, she suffers from many diseases, most notably broken heart syndrome, high blood pressure, diabetes, cancer, weakened immunity, and impaired thyroid function, sometimes leading to thyroid failure, among other illnesses. Psychologically, it causes her to lose her desire for life and happiness because her female hormones are linked to her temperament, making her ineffective within the family and society. Furthermore, constant sadness can lead to depression, anxiety, and sometimes even suicide. The third section: In it, we discussed the impact of treating her kindly and gently. The Islamic religion has made it clear that it does not condone sadness towards her, forbids harming her, and urges honoring her, because she is the source of growth, giving, and goodness. Treating her well, with affection and love, strengthens her self-confidence and gives her the motivation to persevere and succeed in life, achieve her goals, endure life’s hardships, and be patient, cooperating with and reconciling with her husband. This is because he gives her the tranquility she needs and removes her fear and anxiety about the future or the unknown, thus adding joy and happiness to her life. In this way, God Almighty’s purpose in creating the universe is fulfilled, which is to populate the earth, increase offspring, and spread goodness. Conclusion and research findings: There is an interconnected relationship between sadness, both linguistically and idiomatically. God (may He be glorified and exalted) mentioned the concept of sadness in the Holy Quran, and the verses clarified that He (may His glory be exalted) does not desire the sadness of women, because their feelings are more intense and profound than those of men. This is also supported by the hadiths of the Prophetic Sunnah and the opinions of scholars. It causes women to suffer from physical and psychological illnesses. It makes her lose the ability to enjoy anything and makes it difficult to concentrate and control the external circumstances that caused her sadness, such as losing a loved one or something, feeling wronged or oppressed, and other reasons. Kindness, affection, and gentleness towards her have a positive effect on her, as they give her happiness, enable her to continue living effectively, and help her fulfill her duties and responsibilities. At the same time, they protect her from making mistakes. A sad and worried woman cannot raise children and nurture future generations. Similarly, a home filled with problems, quarrels, and poor relationships among its members will not produce healthy, capable children who can serve their society and contribute to the prosperity of their country. Moreover, their personalities will be complex, and they will often suffer from psychological illnesses. 6- List of sources and references.